El marketing educativo y la calidad de servicio de la empresa TESIDE S.A.C. - Badajoz De La Cruz, Mayra Ysabel (2020)
Today, educational marketing has a fundamental role in optimizing the academic offer, has become the necessary engine of change to attract students and promote educational innovation and thus contribute to improving the quality of service. Therefore, this research aimed to identify the relationship between educational marketing and the quality of service of the educational company Teside S.A.C. in the district of Miraflores in 2019, for which the technique was applied to a sample of 100 undergraduate graduates who took advice in the company under study and the results showed a strong positive correlation, making known that educational marketing is an important business strategy to the extent that the quality of service is based on a progressive benefit and duly identified in the undergraduate graduate.